Impact of Persistent Medication Adherence and Compliance with Lifestyle Recommendations on Major Cardiovascular Events and One-Year Mortality in Patients with Type 2 Diabetes and Advanced Stages of Atherosclerosis: Results From a Prospective Cohort Study - Evgeniya V. Shalaeva; Arjola Bano; Ulugbek Kasimov; Bakhtiyor Janabaev; Markus Laimer; Hugo Saner (Ubiquity Press, 2023)
Background: The aim of this study was to evaluate the impact of single and combined effects of persistent medication adherence and compliance with lifestyle recommendations on the incidence of major adverse cardiovascular events (MACE) and one-year all-cause mortality in patients with type 2 diabetes (T2D) and peripheral artery disease (PAD) after partial foot amputation (PFA), representing a unique cohort of patients with advanced stages of atherosclerosis. Methods: This is a prospective cohort study of 785 consecutive patients (mean age 60.9 ± 9.1 years; 64.1% males). Medication adherence was evaluated by using the proportion of days covered (PDC) measure calculation and was defined as a PDC ≥80%. It derived as an average of PDCs of the following four classes of drugs: a) antidiabetics (oral hypoglycemic medications and/or insulin); b) ACEI or ARBs; c) Statins; d) antiplatelet drugs. Lifestyle compliance was defined as a PDC ≥80% comprising of PDCs of a) physical activity of ≥30 minutes per day; b) healthy nutrition and weight management; c) non-smoking. Cox proportional hazard models adjusted for confounders were used. Results: Total all-cause mortality was 16.9% (n = 133) at one-year follow-up. After adjusting for confounders, compared to adherent/compliant patients (n = 432), non-adherent and/or non-compliant patients had an increased risk of one-year mortality: HR = 8.67 (95% CI [5.29, 14.86] in non-adherent/non-compliant patients (n = 184), p < 0.001; HR = 3.81 (95% CI [2.03, 7.12], p < 0.001) in adherent/non-compliant patients (n = 101) and HR = 3.14 (95% CI [1.52, 6.45] p = 0.002) in non-adherent/compliant patients (n = 184). The incidence of MACE followed similar pattern (HR = 9.66 (95% CI [6.55, 14.25] for non-adherence/non-compliance; HR = 3.48 (95% CI [2.09, 5.77] and HR = 3.35 (95% CI [1.89, 5.91], p < 0.001 for single adherence or compliance. Conclusions: Medication adherence and compliance to lifestyle recommendations have shown to be equally effective to reduce the incidence of MACE and one-year mortality in patients with diabetes and PAD after PFA representing a population with highly advanced stages of atherosclerotic disease. Our findings underline the necessity to give lifestyle intervention programs a high priority and that costs for secondary prevention medications should be covered for patients under these circumstances. Lay Summary • This study analyzed the single and combined effects of medication adherence and compliance with lifestyle recommendations on cardiovascular events and mortality in patients with type 2 diabetes and advances stages of atherosclerosis over a period of one year. • Evaluation of medication adherence included antidiabetics, statins, dual antiplatelets and ACEI/ARBs, whereas lifestyle recommendations included healthy nutrition, physical activity and smoking cessation. • Persistent medication adherence and lifestyle changes have shown to be equally effective to reduce the incidence of MACE and one-year mortality in patients representing a population with highly advanced stages of atherosclerotic disease, and positive effects added up to a double effect if patients were persistently adherent and compliant with both interventions.